Una investigación educativa y transformadora para el medio ambiente Desarrollo de capacidades en Guatemala y Nicaragua. Con aportaciones de Maurizio Leonelli y Rodolfo Glenton - Del Gobbo, Giovanna (Studies on Adult Learning and Education, 2018)
There are three major emergencies that characterize the contemporary global world: climate change, agriculture, and waste management. Each of them shows specific characteristics, but they are all part of the same problem: the development model". The volume opens with this quote from Vittorio Cogliati Dezza. Investing in capacity building is one of the strategic keys to face the challenges of a sustainable future, as stated in the 2030 Agenda, aiming to transform, through a long-term vision, the paradigm of dominant development. Within this framework, the volume aims to offer operational elements to address the issue of Capacity building and define the territory as a space of conflicts, governability, agreement and participation undergoing constant change. Thus, participatory territorial planning -a mere technical instrument in itself- becomes a space for awareness, appropriation and leadership of the population. In these processes, the educational dimension assumes a central role, which allows to identify the educational value and the transforming potential of the participation spaces to solve environmental issues, thus improving the social and living conditions of the population.